Assessment of technogenic impact on the environment of the Karaganda region (Journal of Geography and Environmental Management, 2024)
The Karaganda Region, known for its extensive industrial activities, including mining, metallurgy, and energy production, faces significant environmental challenges. These industries, vital for the region's economic development, are also major sources of pollution, contributing to air, water, and soil contamination. The assessment of the technogenic impact is crucial for understanding the extent of environmental degradation, identifying the primary sources of pollution, and developing strategies to mitigate these effects.The article presents an analysis of the technogenic impact on the environment of the Karaganda region. The study is based on the analysis of statistical data, the results of practical research and the application of modern methods.The study identifies the anthropogenic challenges facing the Karaganda region, particularly heavy metal pollution from the mining and metallurgical industries, as well as contributions from the automotive sector and thermal power plants. It uses environmental performance data for linear scaling. As a result of the study, regions that made a significant contribution to environmental pollution were identified, a map of environmental emissions was created, and recommendations were proposed for improving the state of the natural environment of the Karaganda region. The presented analysis will allow us to better understand the nature of anthropogenic impact on the environment and develop recommendations for minimizing it to preserve environmental well-being.
Keywords: technogenic impact, environmental management, emissions, Karaganda region, sustainable development.